First in vivo analysis of the regulatory protein CP12 of the model cyanobacterium Synechocystis PCC 6803: Biotechnological implications - Blanc-Garin, Victoire; Veaudor, Théo; Sétif, Pierre; Gontero, Brigitte; Lemaire, Stéphane D.; Chauvat, Franck; Cassier-Chauvat, Corinne (Frontiers in Plant Science, 2022)
We report the first in vivo analysis of a canonical CP12 regulatory protein, namely the unique CP12 of the model cyanobacterium Synechocystis PCC 6803, which has the advantage of being able to grow photoautotrophically, mixotrophically and heterotrophically. The data showed that CP12 is dispensable to cell growth under standard (continuous) light and light/dark cycle, whereas it is essential for the catabolism of exogenously added glucose that normally sustains cell growth in absence of photosynthesis. Furthermore, to be active in glucose catabolism, CP12 requires its three conserved features: its AWD_VEEL motif and its two pairs of cysteine residues. Also interestingly, CP12 was found to regulate the redox equilibrium of NADPH, an activity involving its AWD_VEEL motif and its C-ter cysteine residues, but not its N-ter cysteine residues. This finding is important because NADPH powers up the MEP (methylerythritol 4-phosphate) pathway that synthesizes the geranyl-diphosphate (GPP) and farnesyl-diphosphate (FPP) metabolites, which can be transformed into high-value terpenes by recombinant cyanobacteria producing plant terpene synthase enzymes. Therefore, we have introduced into the Δcp12 mutant and the wild-type (control) strain our replicative plasmids directing the production of the monoterpene limonene and the sesquiterpene bisabolene. The photosynthetic production of both bisabolene and limonene appeared to be increased (more than two-fold) in the Δcp12 mutant as compared to the WT strain. Furthermore, the level of bisabolene production was also higher to those previously reported for various strains of Synechocystis PCC 6803 growing under standard (non-optimized) photoautotrophic conditions. Hence, the presently described Δcp12 strain with a healthy photoautotrophic growth and an increased capability to produce terpenes, is an attractive cell chassis for further gene manipulations aiming at engineering cyanobacteria for high-level photoproduction of terpenes.